DNA repair gene XPD and XRCC1 polymorphisms and the risk of febrile neutropenia and mucositis in children with leukemia and lymphoma - BARIŞ, SAFA (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
The aim of the study is to investigate association between DNA repair gene XPD and XRCC1 polymorphisms and febrile neutropenia (FN) and mucositis. The study population consisted of 29 children with Burkitt lymphoma and 61 children with acute lymphoblastic leukemia. Analysis revealed that XRCC1194Trp allele showed a protective effect against longer FN and mucositis. There was also statistically increased risk for severe mucositis in patients with XRCC1Arg399Gln polymorphism. There are no studies that have examined this relationship before. Further studies with larger cohorts are needed to clarify the association. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Febrile neutropenia; XRCC1 and XPD polymorphisms; Mucositis; CANCER; ASSOCIATION; IMMUNODEFICIENCY; SUSCEPTIBILITY; CHEMOTHERAPY; RADIOTHERAPY; MORTALITY; TOXICITY; CAPACITY; ERCC2